Development of an iron-metal organic Framework-based dispersive solid phase extraction coupled with flame atomic absorption spectrophotometry for the accurate and sensitive determination of copper in lion's claw tea samples - Semerci, Zeynep Tekinn; Karakebap, K. Ubra; Nur Karaman, Devrim; Yilmaz, Eylul; Dalgic Bozyigit, Gamze; Ozturk, Elif E. R.; Bakirdere, Sezgin (ROYAL SOC CHEMISTRY, 2025)
An iron-based metal organic framework (Fe-MOF) constructed using terephthalic acid as an organic linker was synthesized and characterized for its implementation in a dispersive solid-phase extraction (dSPE) procedure. This strategy was combined with a flame atomic absorption spectrophotometry (FAAS) system and employed for the preconcentration and trace level detection of copper in lion's claw tea samples. Under optimal conditions, the Fe-MOF based dSPE-FAAS method achieved a limit of detection (LOD) of 2.0 mu g L-1 and a limit of quantification (LOQ) of 6.7 mu g L-1. The determination coefficient (R-2) was found to be 0.9984 for the concentration range of 5.0-100 mu g L-1, indicating superior linearity for the developed Fe-MOF-dSPE-FAAS method. The sensitivity was enhanced by 88.2 folds. Moreover, acceptable recovery percentages at five different spiked levels within the concentration range of 7.5-75 mu g L-1 for the lion's claw tea sample matrix were achieved through the application of a matrix matching strategy.
Keywords: DROP MICROEXTRACTION; TRACE AMOUNTS; PRECONCENTRATION; IONS; NANOCOMPOSITE; CADMIUM; PLASMA; WATER; ZINC; LEAD; Chemistry; Food Science & Technology; Spectroscopy